2018
DOI: 10.1055/s-0038-1660839
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Magnetic Resonance Arthrography in Detecting Intra-articular Pathology Associated with Femoroacetabular Impingement

Abstract: Purpose  The aim of this study was to assess the diagnostic accuracy of magnetic resonance arthrography (MRA) in the detection of intra-articular lesions of the hip in patients affected by femoroacetabular impingement (FAI) by using arthroscopy as reference standard. Methods  Twenty-nine consecutive hip arthroscopies performed in 24 patients were considered for the study. Patients had a mean age of 38.3 years. Ultrasound-guided 1.5-T MRA was performed with precontrast short tau inversion recovery, T1-weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…After a systematic search in the above databases, 68 studies were initially selected, and finally, twenty-two studies were included according to the inclusion and exclusion criteria, including 1670 participants [ 4 25 ]. Of the twenty-two studies for the meta-analysis, nineteen studies reported diagnostic results for MRA [ 4 6 , 8 21 , 23 , 25 ] and ten studies reported diagnostic results for MRI [ 4 , 7 , 9 , 13 , 15 , 16 , 20 , 22 24 ]. One study reported the diagnostic results for MRI with a large field of view (LFV) and a small field of view (SFV) respectively [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a systematic search in the above databases, 68 studies were initially selected, and finally, twenty-two studies were included according to the inclusion and exclusion criteria, including 1670 participants [ 4 25 ]. Of the twenty-two studies for the meta-analysis, nineteen studies reported diagnostic results for MRA [ 4 6 , 8 21 , 23 , 25 ] and ten studies reported diagnostic results for MRI [ 4 , 7 , 9 , 13 , 15 , 16 , 20 , 22 24 ]. One study reported the diagnostic results for MRI with a large field of view (LFV) and a small field of view (SFV) respectively [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the QUADAS-2 criteria, most studies presented a low risk of bias and concern regarding applicability. Only one study in which the reference standard results were interpreted without knowledge of the results of the index test [ 21 ]. Besides, six studies were unclear as to whether the index test results were interpreted without knowledge of the results of surgical findings [ 4 , 6 , 10 , 17 , 18 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation